2022
DOI: 10.1039/d2cp01848a
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic stability of Pd–Ru alloy nanoparticles: combination of density functional theory calculations, supervised learning, and Wang–Landau sampling

Abstract: Solid-solution alloy nanoparticles (NPs) comprising Pd and Ru, which are immiscible in the bulk state, have been synthesised and show excellent catalytic performance. To date, most studies have evaluated the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
2
2
0
Order By: Relevance
“…In the Pd-or Ru-rich conditions, the alloy tends to be more stable. The results calculated by PFP in this work is in good agreement with previous work using DFT [21].…”
Section: Excess Energysupporting
confidence: 91%
See 2 more Smart Citations
“…In the Pd-or Ru-rich conditions, the alloy tends to be more stable. The results calculated by PFP in this work is in good agreement with previous work using DFT [21].…”
Section: Excess Energysupporting
confidence: 91%
“…The lowest is for Pd64Ru192 (about 1300K) and the highest is for Pd192Ru64 (3400 K). In the case of Pd128Ru128, the transition temperature is about 2400 K. Comparing these values with the results of previous work in which the total energy was calculated using supervised learning [21], it was found that the transition temperatures for the three compounds in this study are higher.…”
Section: Thermodynamic Propertiessupporting
confidence: 77%
See 1 more Smart Citation
“…Considering the small size and the interaction with the silica support, the trends in selectivity and thermal stability may be influenced by the nanosizing and support effects. To obtain the insights closer into the real HEI/SiO 2 catalyst, more sophisticated theoretical studies based on a supported nanoparticle model are preferred. Although modeling and studying such a complex system are highly challenging, success in this approach will advance the chemistry of HEI-based catalysis.…”
Section: Resultsmentioning
confidence: 99%